Factors associated with Oral Health Related Quality of Life of children with severe -Early Childhood Caries - Shahnaz Mansoori; Abhishek Mehta; Mohd. Irfan Ansari (Journal of Oral Biology and Craniofacial Research)
Background: Early Childhood Caries (ECC) is a chronic childhood disease affecting children worldwide. Severe cases of ECC can significantly affect child's Oral Health Related Quality of Life (OHRQoL) owing to its consequences. The purpose of present study was to find out association between severe early childhood caries (s-ECC) and OHRQoL of children and their parents/care-givers visiting a Government dental hospital in Delhi, India. Methods: Data was collected from a hospital - based sample of 454 child-parent pair. OHRQoL of the child and parent was assessed using the Hindi version of Early Childhood Oral Health Impact Scale (Hi-ECOHIS). Children with s-ECC were identified as per definition given by American Academy of Paediatric Dentistry. Chi square test and Binary regression analysis were used to evaluate the effect of s-ECC on OHRQoL and to study role of various socio demographic factors. Results: The prevalence of s-ECC was 77.1% (n = 350).The mean dmft index score was 5.67 ( ±3.72) and dmfs was 11.21 ( ±11.03). The mean overall ECOHIS score was 7.02 ( ±5.47). Child impact items such as Pain, fever, caries associated swelling along with difficulty in eating food, halitosis, disturbed sleep, frequent absenteeism from school were found to be more significantly more frequent in children with s-ECC than ECC. Children with bottle-feeding habit of more than one year, having fewer siblings, and whose parents belong to upper socio economic class were at higher odds of suffering from s-ECC.Conclusion: s-ECC has significantly more detrimental impact on the OHRQoL of children and their parents in comparison to ECC.